THE ROLE OF VILLAGE GOVERNMENT IN SUPPORTING VILLAGE-OWNED ENTERPRISES (BUMDES) AS A VILLAGE ECONOMIC STRENGTHENER IN BALONGBENDO DISTRICT, SIDOARJO - Khasan, Khafidz; Sunarya , Aris; Kamariyah, Sri (International Journal of Multidisciplinary Reseach, 2025)
Village-Owned Enterprises (BUMDes) are an important tool for strengthening the village economy, the success of which is highly dependent on the role of the village government. This study aims to analyze the contribution of village governments in supporting the management and development of BUMDes, identify factors that hinder the optimization of this role, and examine the extent to which local regulations such as Regional Regulations (Perda) and Regent Regulations (Perbup) of Sidoarjo Regency can serve as a strategic foundation for strengthening the function of BUMDes as drivers of the village economy. This study adopts a qualitative approach with a case study design located in Balongbendo District, Sidoarjo Regency. Data were obtained through in-depth interviews, observations, and analysis of village planning documents, BUMDes reports, and relevant regulations. The research findings indicate that village governments have played a crucial role through planning, facilitating, fostering, and supervising BUMDes, but this role has not been maximized due to limited human resource capacity, weak synergy between institutions, and low community participation. While local regulations provide a sufficient legal basis, they have not been fully utilized strategically in BUMDes management. This study emphasizes the need to strengthen village government capacity and optimize the implementation of local regulations to promote the sustainability of BUMDes as the foundation of the village economy.